Cardiac function in pregnant women with a Fontan circulation following live birth. (25th November 2020) - Lodge, F; Castleman, J; Fox, C; Morris, R.K; Ram, C; Clift, P; Hudsmith, L
Abstract: Background: Fontan circuits are used to palliate congenital heart disease where patients have a single functioning ventricle. The venous return to the heart is redirected to the pulmonary arteries through the use of a conduit, bypassing the heart. Many females with Fontan circuits are now reaching child-bearing age and some desire pregnancy. However, pregnancy in women with Fontan circuits is associated with high complication rates. Purpose: We compared postnatal cardiac function in women with a Fontan circulation with pre-pregnancy cardiovascular investigations. Methods: Data were collected from case notes of all women with a Fontan circulation giving birth after 24 weeks of gestation at Birmingham Women's Hospital between 1997 and 2019. Results: 18 women with a median age of 29±6 years were followed up for 8.0±9 years. There were 21 live births at a median gestation of 32±5 weeks, of which 81% were caesarean sections. Three infants (14%) were born before 30 weeks' gestation and only two (10%) at term. Significant dyspnoea complicated 19% of pregnancies and postpartum haemorrhage occurred in 24%. Pre-pregnancy cardiac magnetic resonance (CMR) data were available for 11 women and post-pregnancy for 14. Post-pregnancy scans were performed a median of 1.5±4.8 years after birth. Ejection fraction was 63.6±5% at baseline and tended to reduce following pregnancy (median −5.0±8%, n=7). Pre-pregnancy peak oxygen consumption (VO2 max) was 73±14% of predicted on cardiopulmonary exercise testing. Median change in VO2 max was −8±22% post-pregnancy (n=4). There was no change New York Heart Association (NYHA) class or resting saturations after pregnancy. Conclusions: Preterm delivery and maternal bleeding were prevalent in this cohort. Exercise capacity was moderately impaired and saturations were typically low. Pregnancy does not seem to have longer term impact on oxygen saturations or NYHA class. Larger series are needed to confirm whether pregnancy is detrimental to postpartum systolic function. CMR can give comprehensive assessment of cardiac function before and after pregnancy and provide data to inform the crucial pre-pregnancy counselling for Fontan patients of child-bearing age. Funding Acknowledgement: Type of funding source: None